Uneven AlGaN multiple quantum well for deep-ultraviolet LEDs grown on macrosteps and impact on electroluminescence spectral output. (26th May 2017) - Kaneda, Michiko; Pernot, Cyril; Nagasawa, Yosuke; Hirano, Akira; Ippommatsu, Masamichi; Honda, Yoshio; Amano, Hiroshi; Akasaki, Isamu
Abstract: AlGaN-based LEDs (λ < 300 nm) fabricated on n-AlGaN templates with a threading dislocation density larger than 5 × 10 8 /cm 2, which were grown on (0001) sapphire with a 1.0° miscut relative to the m -plane, showed external quantum efficiencies (EQEs) of 3.5, 3.9, 6.1, and 6.0% at 266, 271, 283, and 298 nm, respectively. These EQE values reveal significantly high internal quantum efficiencies (IQEs). This performance was obtained using an uneven multiple quantum well (MQW) grown on the AlGaN template with macrosteps having height larger than the well thickness. The electroluminescence spectra of the fabricated LEDs using this MQW structure shifts to a longer wavelength compared with those on sapphire with a miscut angle of 0.3° relative to the m -plane. Furthermore, the LEDs with this MQW show no deleterious effect on the lifetime, broader electroluminescence spectral widths, and higher output powers when using sapphire with a miscut of 1.0°.